2021
DOI: 10.1101/2021.04.08.21255106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adipose tissue distribution from body MRI is associated with cross-sectional and longitudinal brain age in adults

Abstract: There is an intimate body-brain connection in ageing, and obesity is a key risk factor for poor cardiometabolic health and neurodegenerative conditions. Although research has demonstrated deleterious effects of obesity on brain structure and function, the majority of studies have used conventional measures such as waist-to-hip ratio, waist circumference, and body mass index. While sensitive to gross features of body composition, such global anthropomorphic features fail to describe regional differences in body… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 99 publications
2
11
0
Order By: Relevance
“…The associations between abdominal adipose tissue and brain characteristics are consistent with previous studies linking elevated adipose tissue to older brain age (Beck et al, 2022;Subramaniapillai et al, 2022), lower brain volume (Cho et al, 2021;Debette & Markus, 2010;Gurholt et al, 2021;Isaac et al, 2011;Veit et al, 2014), and higher WMH load (Arnoldussen et al, 2019;Lampe et al, 2019;Park et al, 2018;Vuorinen et al, 2014). The relationships were strongest for WMH volume, suggesting that brain white matter may be particularly sensitive to elevated abdominal adipose tissue in post-menopausal females.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The associations between abdominal adipose tissue and brain characteristics are consistent with previous studies linking elevated adipose tissue to older brain age (Beck et al, 2022;Subramaniapillai et al, 2022), lower brain volume (Cho et al, 2021;Debette & Markus, 2010;Gurholt et al, 2021;Isaac et al, 2011;Veit et al, 2014), and higher WMH load (Arnoldussen et al, 2019;Lampe et al, 2019;Park et al, 2018;Vuorinen et al, 2014). The relationships were strongest for WMH volume, suggesting that brain white matter may be particularly sensitive to elevated abdominal adipose tissue in post-menopausal females.…”
Section: Discussionsupporting
confidence: 88%
“…The relationships between oestrogen exposure, body composition, and brain health in females are complex and largely unexplored. The menopause transition is linked to an accelerated increase of central fat accumulation (Lizcano & Guzmán, 2014), and abdominal adipose tissue has been associated with higher grey matter (GM) and white matter (WM) brain age (Beck et al, 2022(Beck et al, , 2021bSubramaniapillai et al, 2022), WM hyperintensities (WMH) (Arnoldussen et al, 2019;Han et al, 2021;Lampe et al, 2019;Pasha et al, 2017;Park et al, 2018;Vuorinen et al, 2014), and dementia risk (Kiliaan et al, 2014;Tang et al, 2021;Razay et al, 2006;Whitmer et al, 2008). However, in females, adipose tissue also serves as the primary biosynthesis site of oestrogens post-menopause (Steiner & Berry, 2022;Bhardwaj et al, 2019;Kershaw & Flier, 2004;Siiteri, 1987;Simpson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While the current study focused on WM measures given their susceptibility to CMRs, future studies may aim to include several brain modalities to directly compare sex‐ and age‐specific effects. More detailed measures of fat distribution obtained with body MRI (Beck, de Lange, Alnaes, et al, 2021 ; Gurholt et al, 2021 ; Leinhard et al, 2008 ; Linge et al, 2018 ) may also clarify the divergent associations observed in females, and provide a more complete understanding of adipose tissue distribution in relation to cardiometabolic disease (Linge et al, 2018 ; Linge et al, 2019 ), AD risk (Diehl‐Wiesenecker et al, 2015 ), and endocrine aging processes (El Khoudary et al, 2015 ). Due to sample size restrictions in relation to our study goals of determining sex‐ and age‐specific effects, we could not currently probe body MRI in our subgroups, but ongoing data collection of this measure from UK Biobank participants will render future analyses of these measures feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Positive BAG values have also been associated with negative outcomes in population‐based studies, including cardiovascular risk, cognitive impairments, and dementia risk (Biondo et al, 2021 ; de Lange, Anatürk, et al, 2020 ; Egorova et al, 2019 ; Franke & Gaser, 2012 ; Gaser et al, 2013 ; Kolbeinsson et al, 2020 ; Löwe et al, 2016 ; Wang et al, 2019 ). Previous studies have shown accurate age prediction based on diffusion‐weighted imaging measures (Beck, de Lange, Maximov, et al, 2021 ; Cole, 2020 ; Richard et al, 2018 ; Voldsbekk et al, 2021 ), as well as associations between WM BAG and CMRs (Beck, de Lange, Alnaes, et al, 2021 ; Beck, de Lange, Pedersen, et al, 2021 ). However, these previous studies did not assess sex‐specific effects, or whether CMRs interact with APOE genotype to influence WM BAG during certain life phases.…”
Section: Introductionmentioning
confidence: 98%
“…ectopic fat tissue) most associated with metabolic disturbances (Bergman et al, 2006;Després and Lemieux, 2006). As BMI is not particularly sensitive to the distribution of body fat, alternative techniques, such as body magnetic resonance imaging (MRI) segmentation, are required to measure the individual contributions of different fat depots (Beck et al, 2021;Gurholt et al, 2021;Linge et al, 2019Linge et al, , 2018. In the current study, we use an oxytocin pathway polygenic score (PGS oxt ) (Winterton et al, 2021) to evaluate the genetic contribution of SNPs belonging to 154 genes attributed to the oxytocin signalling pathway on cardiometabolic risk factors, including body fat distribution and infiltration indexed via body MRI, haematological markers, blood pressure, and bone mineral density in a large sample of adults from the UK Biobank.…”
Section: Introductionmentioning
confidence: 99%